Innovation Capability Mediates Factors Determining Sustainable Entrepreneurial Performance - I Nengah Suardhika; Putu Kepramareni (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
Sustainable entrepreneurial performance has become increasingly critical for the long-term survival of SMEs in the culinary sector, especially as these businesses face mounting competitive pressures while contributing significantly to the national economy. Previous research has examined entrepreneurial bricolage and digital marketing capability in isolation, yet we know little about how these two capabilities interact to drive sustainable performance outcomes. This study addresses this gap by investigating their combined effects through innovation capability as a mediating mechanism, providing fresh perspectives on how resource-constrained SMEs can achieve lasting success. We employed a quantitative cross-sectional design, surveying 270 culinary SMEs across Bali Province and analyzing the data through PLS-SEM. Our findings reveal an interesting pattern: entrepreneurial bricolage directly enhances sustainable performance, whereas digital marketing capability shows no significant direct impact. The mediating role of innovation capability proves crucial—it partially channels the effect of entrepreneurial bricolage while completely mediating the influence of digital marketing capability on performance outcomes. These results support the integration of bricolage theory and dynamic capability theory within the culinary SME context. The evidence suggests that digital marketing capability must first be converted into tangible innovation before it can contribute to sustainable performance. Meanwhile, the bricolage approach demonstrates versatility by affecting business sustainability both directly and indirectly through innovation. This distinction offers practical implications: SMEs should leverage their resourcefulness immediately while simultaneously transforming their digital capabilities into concrete innovations to secure long-term competitive advantage.